2022
DOI: 10.3390/s22134787
|View full text |Cite
|
Sign up to set email alerts
|

Raspberry Shake-Based Rapid Structural Identification of Existing Buildings Subject to Earthquake Ground Motion: The Case Study of Bucharest

Abstract: The Internet of things concept empowered by low-cost sensor technologies and headless computers has upscaled the applicability of vibration monitoring systems in recent years. Raspberry Shake devices are among those systems, constituting a crowdsourcing framework and forming a worldwide seismic network of over a thousand nodes. While Raspberry Shake devices have been proven to densify seismograph arrays efficiently, their potential for structural health monitoring (SHM) is still unknown and is open to discover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 76 publications
1
5
0
Order By: Relevance
“…Based on the numerical test results for shake table testing under 60 Hz frequency, it was observed that the vibrations were found lower at bottom storey as compared to top storey. Similar results were also observed by previous works [15,16]. The peak positive acceleration was found to be 4.72, 3.03 and 1.93 g at 3 rd , 2 nd and 1 st floor respectively.…”
Section: Analysis Of the Numerical Acceleration Data Outputsupporting
confidence: 91%
See 1 more Smart Citation
“…Based on the numerical test results for shake table testing under 60 Hz frequency, it was observed that the vibrations were found lower at bottom storey as compared to top storey. Similar results were also observed by previous works [15,16]. The peak positive acceleration was found to be 4.72, 3.03 and 1.93 g at 3 rd , 2 nd and 1 st floor respectively.…”
Section: Analysis Of the Numerical Acceleration Data Outputsupporting
confidence: 91%
“…Low-cost micromechanical systems (MEMS) system has been widely used for structural and geotechnical applications [12][13][14][15][16][17][18][19]. Choudhry B.S.…”
Section: Introductionmentioning
confidence: 99%
“…All this, together with the growing development of microcontrollers and open-source electronic platforms, has led to the development of ad hoc seismic recorders by some researchers. Many of them are focused on the measurements of a vertical sensor, e.g., [ 22 , 23 ], the measurements of three components for subsequent H/V analysis, e.g., [ 24 , 25 , 26 ], geophysical exploration, e.g., [ 27 , 28 ], seismic monitoring in buildings, e.g., [ 29 , 30 , 31 ], etc.…”
Section: Introductionmentioning
confidence: 99%
“…In this work we present our study regarding lab and field testing of a low-cost 3C seismometer that could foster the development of shallow passive seismic applications. Recently, this unit, or similar ones produced by the same manufacturer, have been employed for different aims, including studying global quieting of seismic noise during COVID-19 pandemic lockdown (Lecocq et al, 2020), densification of seismic networks with the so-called citizen Seismology (Calais et al, 2022;Walter et al, 2019), monitoring of rockfalls (Manconi et al, 2018), induced seismicity (Hicks et al, 2019), icequakes (Winter et al, 2021) and structural health (Alarcón et al, 2023;Özcebe et al, 2022). Anthony et al (2019) have analyzed the performance of a seismic station similar to the one considered here, though addressing seismological applications.…”
mentioning
confidence: 99%